Comparative study Between intracapsular microdebrider tonsillectomy and extracapsular conventional surgical tonsillectomy - Mohamed Sherif Abd Elmonem; Ashraf Khaled; Mostafa Hashim; Rabie Youssef (Egyptian Journal of Medical Research, 2023)
Aim and objectives: Evaluation of the efficacy of intracapsular microdebrider tonsillectomy in comparison to extracapsular conventional surgical tonsillectomy regarding timing, postoperative pain, amount of blood loss, tonsillar fossa healing and complications. Methods: Controlled, prospective, and comparative study was done on 25 patients (14 female and 11 male) aged from 4-12 years old. Those patients received intracapsular microdebrider tonsillectomy on the left side and conventional extracapsular surgical tonsillectomy on the right side. Results: Intracapsular microdebrider tonsillectomy had a significant less pain post tonsillectomy, there was a great difference between the two sides. On our study we did the two techniques on the same person, and this helped us to know the difference between the two techniques in pain on the same body mass index, while we found that no statistically difference between the two techniques in timing, volume of blood loss during operation, wound healing, and complications Conclusions: Intracapsular microdebrider tonsillectomy was comfortable, safe, and effective procedure, we motivate other surgeons to add to our experience with microdebrider intracapsular tonsillectomy.